On a curvature flow model for embryonic epidermal wound healing. (December 2019) - He, Shuhui; Wheeler, Glen; Wheeler, Valentina-Mira
Abstract: The paper is a mathematical investigation of a curvature flow model for embryonic epidermal wound healing proposed by Ravasio et al. (2015). Under the flow we show that a closed, initially convex or close-to-convex curve shrinks to a round point in finite time. We also study the singularity, showing that the singularity profile after continuous rescaling is that of a circle. One of the key new results we require is a maximal time estimate, which is also of independent interest.